2020
DOI: 10.3389/fpsyg.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Social Impact of a Transformative Service-Learning Experience in a Post-conflict Setting

Abstract: In the context of the 2016 Peace Agreement signed between the Colombian government and the FARC-EP (Fuerzas Armadas Revolucionarias de Colombia-Ejército del Pueblo), several challenges for society and academia have emerged: (1) overcoming the gap between the rural and urban settings, which has been one of the roots of the Colombian armed conflict, and (2) training psychologists and transforming traditional educational practices, which have not been designed to fulfill community needs in a post-conflict setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…Another meta-analytic review of 40 studies involving 5495 participants found that SL promoted understanding of community needs, personal understanding, and cognitive competence, although some moderating factors were also identified (Yorio and Ye 2012). There are also some recent studies on the impact of SL on civic engagement: Mason and Dunens (2019) reported that SL could promote student learning and achieving the foundational knowledge in public health; Trigos-Carrillo et al (2020) highlighted the ability of service learning experience to transform students' cultural humility and affective understanding in postconflict setting. However, it is noteworthy that there are cautions about the "dark side" of SL (Eby 1998;Morin 2009) such as whether it promotes social justice or social stagnation.…”
mentioning
confidence: 99%
“…Another meta-analytic review of 40 studies involving 5495 participants found that SL promoted understanding of community needs, personal understanding, and cognitive competence, although some moderating factors were also identified (Yorio and Ye 2012). There are also some recent studies on the impact of SL on civic engagement: Mason and Dunens (2019) reported that SL could promote student learning and achieving the foundational knowledge in public health; Trigos-Carrillo et al (2020) highlighted the ability of service learning experience to transform students' cultural humility and affective understanding in postconflict setting. However, it is noteworthy that there are cautions about the "dark side" of SL (Eby 1998;Morin 2009) such as whether it promotes social justice or social stagnation.…”
mentioning
confidence: 99%
“…Third, providing emergency medicine specialists and trainees opportunities for medical care encounters with FARC ex‐combatants could increase knowledge of this population, and position emergency medicine to take an active role in the FARC peace process. This could start as early as the student or trainee level, as non‐health programs have demonstrated successes in facilitating encounters between students and reincorporating FARC, 12 and the mandatory year of service ( Servicio Social ) provides an avenue for these encounters with medical brigades in heavily FARC and former conflict areas. ACEM ( Asociación Colombiana de Especialistas en Medicina de Urgencias y Emergencias ) has an opportunity as the Colombian emergency medicine professional network to actualize such interventions, such that emergency medicine professionals have the opportunities and feel better prepared to care for FARC ex‐combatants and other vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a cornerstone aspect of FARC reincorporation was access to healthcare, offered by a specialized health insurance provider, or EPS ( Entidad Promotora de Salud) at little cost to ex-combatants [ 8 ]. The FARC (or Farian) community was estimated to have disproportionately high healthcare needs due to unmanaged chronic conditions, infectious diseases, and undiagnosed mental health trauma from the conflict [ 9 11 ]. The peace agreement with the FARC promised to strengthen health systems in rural areas where healthcare access has historically been limited [ 12 ]; including reinforcing infrastructure, implementation of telemedicine, differential approaches for gender-specialized care, and a focus on prevention and health promotion [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peace agreement with the FARC promised to strengthen health systems in rural areas where healthcare access has historically been limited [ 12 ]; including reinforcing infrastructure, implementation of telemedicine, differential approaches for gender-specialized care, and a focus on prevention and health promotion [ 8 ]. With this agreement, 24 Espacios Territoriales de Capacitación y Reincorporación (ETCRs), or Territorial Spaces for Training and Reintegration, were established in 16 Departments of Colombia [ 9 ], where approximately 8200 FARC have lived and utilized reincorporation services offered by the Colombian government [ 13 ].…”
Section: Introductionmentioning
confidence: 99%